Improving the pre-employment process of Chevron Holdings Inc. - Manila Shared Services Center - Lerma, Angelica Faye P. (Animo Repository, 2016)
This action research aims to address the issues on negative job candidate experience and long turn-around-time of the pre-employment process as caused by the obsolete list of pre-employment requirements and cumbersome pre-employment process in the Human Resource Department of the Manila Shared Services Center of Chevron Corporation. The Action Research Cycle of Coghlan and Brannick was employed as guide through the course of the study. Methods of Inquiry and Collaboration such as Search Conference, Email Communications, Informal Discussions and Focused Group Discussions were conducted throughout the action research cycles to gather and analyze data. Steps of the DMAIC framework were followed to deal with the process side of change, in conjunction with the ADKAR framework to deal with the people side of change. Theories and concepts such as Lean Six Sigma, Honshin Kanri, Deming Cycle, Participatory Management, Adaptive Cycle and Helix Methodology were applied in the analysis to arrive at solutions. Through collaboration among the Staffing, HR Administration and Payroll teams, and after two action research cycles, unnecessary requirements were eliminated and non-value adding steps were removed, therefore improving the efficiency of the pre-employment process for both the new hires and the processors. As a contribution to the larger society, synthesis of the management theories & personal reflections & learnings, and social development principles are integrated to create relevance for other companies or organizations that are yet to undergo a similar process of change or improvement, while still being conscious of the three pillars of a corporate mission - people, planet and profit.